Improvement of the bending behavior of a flexible riser : Part I – nonlinear bending behavior considering the shear deformation of polymer layers. (August 2020) - Yun, Ran-Hui; Jang, Beom-Seon; Kim, Jung Du
Highlights: w This paper proposes an analytical model for the prediction of nonlinear bending behavior of flexible risers. w The proposed analytical model formulates the stress of tensile armor layers through the equilibrium equations which take into account the shear deformation and radial deformation of polymer layers. w Using a linear differential equation of each component of flexible risers, the analytical model reflects the shear interaction force between layers and contact pressure induced by bending into the equilibrium equations, deriving accurate bending hysteresis curves as a function of curvature and axisymmetric loads. w The validity of the proposed model is examined by comparing the results of the analytical model with the FE analysis results, and a case study on various combined load cases performed for in-depth understanding. Abstract: An un-bonded, multi-layered assembly of heterogeneous materials in the cross-section of flexible risers enables riser systems to withstand a large radius of curvature while preventing structural damage or buckling of many critical areas such as a touch down zone. The contact surfaces between layers exhibit a continuous sliding of metallic components after a certain level of bending, which lowers the bending stiffness of flexible risers. Such interactions are beneficial in order to reduce the stress of tensile wires, but complicate prediction of the limit state and fatigue damage of riser systems in that the sliding of metal layers involves a complex contact phenomenon that is difficult to solve numerically. This series of papers deals with the development of an improved analysis method for flexible risers using theoretical approaches. Part I, as presented in these pages, develops an analytical model that is capable of estimating the cross-sectional stiffness of flexible risers with consideration of external loads and inter-layer interaction. In Part II, the proposed analytical model is applied to a large-scale riser model to achieve an efficient global dynamic analysis of flexible risers. This paper, the first part of a two-paper series, proposes an analytical model that formulates the stress of tensile armor layers through equilibrium equations that take into account the shear and radial deformation of polymer layers. The equilibrium equations are derived under a linear differential equation for each component of flexible risers, so that not only the shear interaction forces but also the contact pressure originating from the bending of layers is considered in the analytical model. The shear interaction forces between two tensile armor layers are formulated through an equivalent shear stiffness by which the shear stiffness of layers is linearly modeled as a series of springs. The proposed model is verified by comparison with the nonlinear bending stiffness from existing bending models and finite element (FE) analysis. For additional verification, the axial stresses of inner and outer tensile armor also are compared. And for further, more in-depth understanding, a case study of various combined load cases is carried out.